Incremental Organizational Learning from Multilevel Information Sources: Evidence for Cross-Level Interactions - Schwab, Andreas (Organization science (Providence, R.I.), 2007)
The availability of both direct performance feedback at the organization level and vicarious information at the industry level raises the question of their relative impact, as well as potential multilevel interactions. Prior research suggests that an organization's own experience after adopting an innovative managerial practice tends to replace information collected by observing other organizations that implement the practice. The findings in this study show, however, that both organization-level performance feedback and population-level comparisons to other organizations affected incremental change of an innovative practice during its execution. The effects of these two information sources are not independent. Instead, results support a substitutional cross-level interaction. In addition, the study discovered that, when learning from their own experience, organizations engage in superstitious learning and do not let sufficient time pass before assessing the effects of prior changes. This study identifies principles that will promote a more integrated understanding of learning during the execution of innovative practices and contributes to the development of more fine-grained multilevel models of organizational learning. [PUBLICATION ABSTRACT]